2009
DOI: 10.1152/ajpendo.00396.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of methionine utilization and splanchnic uptake in critically ill children

Abstract: -To determine the rates of methionine splanchnic uptake and utilization in critically ill pediatric patients we used two kinetic models: the plasma methionine enrichment and the "intracellular" homocysteine enrichment. Twenty four patients, eight infants, eight children, and eight adolescents, were studied. They received simultaneous, primed, constant, intravenous infusions of L-[ 2 H3]methylmethionine and enteral L-[1-13 C]methionine. The ratio of [13 C]homocysteine to [ 13 C]methionine enrichment was 1.0 Ϯ 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Protein accretion will not occur without a sufficient energy supply, and a sufficient energy supply will not support anabolism in the absence of adequate protein (nitrogen) intake. We have shown that the parenteral protein requirements of critically ill children have been based on limited data (13) and that, at currently recommended enteral protein intakes, critically ill pediatric patients remain in significantly negative protein balance (14).…”
Section: 6-2 H 2 ]Glucose and [11233-2 H 5 ]Glycerol In Combimentioning
confidence: 99%
See 1 more Smart Citation
“…Protein accretion will not occur without a sufficient energy supply, and a sufficient energy supply will not support anabolism in the absence of adequate protein (nitrogen) intake. We have shown that the parenteral protein requirements of critically ill children have been based on limited data (13) and that, at currently recommended enteral protein intakes, critically ill pediatric patients remain in significantly negative protein balance (14).…”
Section: 6-2 H 2 ]Glucose and [11233-2 H 5 ]Glycerol In Combimentioning
confidence: 99%
“…Hyperglycemic (Ͼ120 mg dL Ϫ1 , Ͼ6.7 mM) adolescents (13-18 yrs of age) with a diagnosis of severe sepsis, septic shock, or systemic inflammatory response syndrome (19) and receiving total parenteral nutrition were considered eligible. Only adolescents aged 13-18 yrs were included in the study as we have previously observed that metabolic processes greatly vary with age (14). All patients had drawing and infusing intravascular catheters and had received complete parenteral feedings for at least 24 hrs before the study.…”
Section: Patientsmentioning
confidence: 99%
“…Studies with methods that did not provide time for adaptation to either the protein or amino acid intakes prior to the study period were also not included. One study (19) met all methodological criteria as described previously but was not included, because the jn.nutrition.org subjects were patients in an intensive care unit and were not comparable to the clinically stable subjects in the studies listed in Table 3. There were 14 studies that qualified for inclusion in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill children have an increased protein turnover due to an increase in whole‐body protein synthesis and breakdown 25 , 38 , 39 . During inflammatory conditions, there is a decrease in protein synthesis at the skeletal muscle level and an increase in protein degradation to shuttle amino acids and nitrogen to the tissues 38 , 40 . Protein degradation can be greater than muscle protein synthesis and create a negative protein balance.…”
Section: Alterations In Protein and Amino Acids During Critical Illnessmentioning
confidence: 99%
“…While these methods are very accurate to measure protein kinetics, they require specialized equipment and expertise to conduct the studies. Several authors have reported the use of stable isotopes to assess protein metabolism and needs in critically ill children 15 , 25 , 26 , 40 , 54 , 115 , 116 …”
Section: Assessment Of Body Composition and Protein Turnover During Cmentioning
confidence: 99%